Empowering future public health professionals: The impact of community-based education on students’ maternal and child health competencies - Rubeena Zakar; Gulzar Shah; Ruhma Shahzad; Nazoora Manal Zakar; Ara Tekian (PLoS ONE, 2026)
Preparing future public health professionals to address real-world maternal and child health (MCH) challenges requires educational approaches that extend beyond classroom instruction. In this context, integrating community-based education (CBE) into the curriculum serves as a pivotal strategy. This study assesses the implementation and effectiveness of a CBE module in MCH, designed for strengthening the knowledge and competencies of undergraduate public health students. A mixed-method pre- and post-intervention design was used to assess changes in students’ knowledge, skills, and practical competencies following one year of supervised community engagement in a semi-urban setting in Lahore, Pakistan. Quantitative assessments included survey questionnaires, quizzes, MCQs, and OSCE, while qualitative data were collected through focus group discussions, and self-reflection logs. Descriptive statistics, a paired-samples t-test, and a marginal homogeneity test were used to assess students’ learning and research outcomes. For qualitative data, thematic analysis was conducted using a deductive-inductive approach. Pre- and post- analysis revealed significant improvements (p < 0.001) in students’ knowledge across all MCH domains, along with enhanced skills of leadership, project/time management, communication, problem-solving, teamwork, handling unexpected situations, and designing community-tailored interventions (p < 0.001) following CBE implementation. Ongoing assessments indicated consistent learning with a mean quiz score of 80.2% (SD = 7.2), and a mean MCQ exam score of 81.5% (SD = 7.6). Qualitative data further revealed increased empathy, cultural sensitivity, and professional confidence. The study concludes that the CBE program provides students with valuable insights into the specific needs and challenges of communities related to MCH, thereby enhancing their knowledge and competency development. This experience supports the continuation of CBE programs for future students.